Trachea Reconstruction with Single-Stage Composite Flaps in a Rabbit Model - Wong, Manzhi; Tan, Bien-Keem; Lim, Chong-Hee (Journal of Reconstructive Microsurgery, 2020)
Background Trachea reconstruction requires creation of a functional lining, semirigid support, and vascularity. We aimed to design composite flaps with these three components in a rabbit model.Methods Circumferential (n = 9) and partial anterior (n = 8) tracheal defects were created in rabbits. A circumferential defect was reconstructed with a tubed ear flap incorporating cartilage for support and skin for lining. This was pedicled on the posterior auricular vessels and tunneled into the neck to bridge the defect. In the second experiment, a longitudinal anterior trachea defect was patched with a pedicled rib cartilage and intercostal muscle flap based on the internal mammary vessels. The vascularized fascia over the intercostal muscles replaced the lining while the cartilage provided support. Postoperatively, the rabbits were monitored clinically and endoscopically. The tracheal constructs were examined histologically after the animals were sacrificed.Results Rabbits with circumferential defects reconstructed with the ear flap survived up to 6 months. Histology demonstrated vascularized cartilage with good integration of the flap with native trachea. However, hair growth and skin desquamation resulted in airway obstruction in the long term. In the second experiment, all the rabbits survived without respiratory distress, and the intercostal muscle fascia was completely covered by native respiratory epithelium.Conclusion We described two experimental techniques using autologous composite flaps for single-stage trachea reconstruction in a rabbit model. Skin was a poor lining replacement, whereas vascularized muscle fascia became covered with respiratory epithelium. A rib cartilage and muscle flap could potentially be used for reconstruction of partial defects in humans.
Keywords: trachea; reconstruction; rabbit